Desigualdades e efeitos desiguais : uma análise da influência das condições socioeconômicas e dos backgrounds familiares sobre a experiência socializadora do Parlamento Jovem de Minas Gerais (2008) - Myla Freire Machado Fernandes (2021)
The relations between the effects of political education and different socioeconomic status and family backgrounds of its participants constitute the theme of this dissertation. This investigation develops from the of 2008 edition of the Youth Parliament of Minas (PJ Minas), a initiative of political education developed by the Legislative Assembly of the State of Minas Gerais since 2004. The research question that arises is the following: does the PJ Minas (2008) produce different effects depending on the socioeconomic conditions and Family backgrounds of its participants? Thus, the objective is to provide, based on such dimensions, a detailed analysis of the effects of the program on political knowledge, political engagement and democratic political attitudes of its members. The hypotheses hold that individuals in disadvantaged socioeconomics situations are those who have the most to gain from political education in these three areas, and also that this compensation effect concentrates on objects salients to the program in the political knowledge and democratic political attitudes, as well as in the motivational dimension of political engagement. Quantitative methodologies are maids, so that the operationalization of the variables use multiples scales and exploratory fator analyzes, while the analysis of the results explores descriptive statistics and multivariate analyzes guided by models of regressions linears and logistics. Although the results seem to reflect different patterns of unequal effects of PJ Minas (2008), the most solid finding of this study relates to the ability of the young person's socioeconomic condition, represented by the type of school he attended, to condition the impact of treatment on cognitive and engagement gains, scenarios in which the effects of the “necessary minimum” and “left behinds” stand out. In this sense, it is young people belonging to the intermediate strata of the socioeconomic hierarchy observed by this research that have the most to gain from the program, while Young people in disadvantaged socioeconomic conditions, even with the intervention of political education, continue being “left behinds” in relation to the others.